(untitled) (LACCEI, 2024)
The objective of this research article is to make a proposal to support decision-making within the sales area in hardware companies. The company La Libertad S.R.L was taken as a case study, applying the use of the business intelligence tool as an effective and efficient solution. For this article, points in the design of the DataMart have been considered, such as the management and analysis in a strategic way in the operational part of the company’s sales area based on the types of products with the highest valuation and / or sale. Currently in the company La Libertad S.R.L., in the sales area, it has a transactional system that performs processes such as the registration of categories, customers, districts, employees, orders, suppliers, stores. This system that goes hand in hand with the database is feasible for the company, however there is no form of visibility of complete movements for the manager of the sales area, either from the current year or from previous years, which is of important interest. for the planning of future projects, and in case of wanting to carry out a project, they must handle visible data to support the marketing and production area. The article aims to develop a DataMart as a business intelligence tool which is a decision support service for Peruvian hardware companies that need to plan their activities and in turn reduce the time it takes to generate reports.